Survival of patients with breast cancer ten years after surgery - Ada Berchi Aguilar; Lidia Torres Ajá; Ernesto Julio Bernal Valladares; Deanna Collazo Cuellar; Neylin Caballero Aja (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Foundation: Breast cancer is considered a health problem worldwide. In Cuba it is a prioritized line of research and treatment. Objective: To characterize the survival of patients with breast cancer at ten years of surgery. Methods: Descriptive Cohort retrospective study developed at the Surgery Service of the General Teaching Hospital Dr. Gustavo Aldereguía Lima, of the Cienfuegos Province within the period from January 2005 to December 2007. A number of 196 patients operated for breast cancer were analyzed by the Kaplan-Meier method over a period of ten years of survival after surgery. Besides the socio-demographic variables, it was analyzed: Affected breast, Tumor location, Histological type, Clinical state at the moment of the operation and surgical technique used. Results: The highest average survival was found in patients aged between 71-80 and over 80 years who had a lobular carcinoma, who had tumors in clinical stage IIa and who were subject to radical mastectomies. Conclusion: The group of patients object of study showed an elevated global survival, which was mainly associated to older ages, the early diagnosis of the disease and the performance of radical surgery.